2019
DOI: 10.1111/evo.13707
|View full text |Cite
|
Sign up to set email alerts
|

Fifty shades of brown: Macroevolution of plumage brightness in the Furnariida, a large clade of drab Neotropical passerines

Abstract: Both natural and sexual selection are thought to affect the evolution of bird color. Most studies of the topic have focused on sexually dichromatic taxa and showy plumages, which are expected to be more influenced by social selection and usually result in increased conspicuousness. However, many bird clades display dull brown or gray plumages that vary greatly in brightness (lightness), but little in hue (shade). Here, we examine the macroevolution of brightness in one such clade, the Furnariida. We make compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 87 publications
(122 reference statements)
10
49
1
Order By: Relevance
“…In contrast, if Gloger’s rule is mainly a result of birds adapting to be darker in darker (forest) habitats, bird species occupying forest habitats are predicted to be darker than their nonforest-based relatives, even if they inhabit similar climatic regimes. Marcondes and Brumfield (2019) previously demonstrated that furnariid species have evolved to be darker in darker habitats, consistent with Endler’s (1993) predictions for crypsis. Here, we sought to investigate the interacting roles of climate and habitat type in driving interspecific variation in plumage brightness in the Furnariidae.…”
supporting
confidence: 78%
See 4 more Smart Citations
“…In contrast, if Gloger’s rule is mainly a result of birds adapting to be darker in darker (forest) habitats, bird species occupying forest habitats are predicted to be darker than their nonforest-based relatives, even if they inhabit similar climatic regimes. Marcondes and Brumfield (2019) previously demonstrated that furnariid species have evolved to be darker in darker habitats, consistent with Endler’s (1993) predictions for crypsis. Here, we sought to investigate the interacting roles of climate and habitat type in driving interspecific variation in plumage brightness in the Furnariidae.…”
supporting
confidence: 78%
“…We used the color dataset previously described in Marcondes and Brumfield (2019) and deposited on the Dryad digital repository under DOI 10.5061/dryad.s86434s (embargoed until July 16, 2021). Briefly, this dataset includes reflectance data for 250 (84%) furnariid species, with an average of 6.4 specimens per species (range: 1-8).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations